A brief history of spaceflight from 1961 to 2020: An analysis of missions and astronaut demographics. (October 2020) - Smith, Michael G.; Kelley, Michelle; Basner, Mathias
Abstract: Human spaceflight and the characteristics of people who become astronauts have changed over time. Here we present an analysis of n = 1265 manned spaceflights by n = 562 astronauts from 1961 to 2020 to investigate historical trends over time and between space agencies in terms of astronaut demographics and spaceflight duration. Generalized linear models and generalized linear mixed models were implemented with adjustments for all available demographic data as covariates. Women continue to be underrepresented as astronauts, and were younger, had fewer children, and were less likely to have a military background than their male counterparts. Astronaut age has increased over time, although this increase was significant only for first-time spaceflights. The proportion of astronauts from civilian backgrounds has generally increased over time, although there is evidence this trend may be reversing. Spaceflight duration has increased over time, and has been longest for ROSCOSMOS cosmonauts and shortest for Chinese taikonauts. There were also differences between space agencies in terms of astronaut demographics, particularly between NASA and ROSCOSMOS, with first-time NASA astronauts more likely to be women, civilian and older than first-time ROSCOSMOS cosmonauts. As humankind embarks on exploration-class missions back to the lunar surface and then onward to Mars, and with new nations and commercial entities entering the international space community, the nature of spaceflight, and the diversity of the astronauts, will continue to evolve. Highlights: Regression analysis of historical spaceflight missions and astronaut demographics. Female astronauts have become more prevalent but remain underrepresented. Astronauts have become older and less likely to have a military background over time. NASA astronauts more likely to be women, civilian and older than ROSCOSMOS cosmonauts. Spaceflight duration has increased and will likely continue to increase in the future.